2005
DOI: 10.1111/j.1365-3180.2004.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy and viability of Phalaris minor seed in a rice–wheat cropping system

Abstract: Summary Seed placement, soil temperature and soil moisture content influenced the process of after‐ripening in Phalaris minor seeds. Seeds of P. minor collected from the soil just after wheat harvesting exhibited higher germination than seeds from P. minor threshed directly. There was a pronounced impact of periodic inhabitation of seed into the soil on germination after its dispersal. Germination was strongly inhibited when the seed was kept in soil at more than field capacity (FC) or in water. Maximum germin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Therefore, factors other than relative moisture distribution, such as soil physicochemical properties, soil temperature and mechanical or light stimulation breaking seed dormancy during ploughing, may have been involved. Om et al. (2005) and Jimenez‐Hidalgo et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, factors other than relative moisture distribution, such as soil physicochemical properties, soil temperature and mechanical or light stimulation breaking seed dormancy during ploughing, may have been involved. Om et al. (2005) and Jimenez‐Hidalgo et al.…”
Section: Discussionmentioning
confidence: 96%
“…These conditions are considered optimal for P. minor germination (Bhan & Choudary, 1976; Singh & Dhawan, 1976; Okereke et al. , 1981; Mehra & Gill, 1988; Om et al. , 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Species of the genus Phalaris require periods of low temperature to break seed dormancy (Om et al, 2005). To determine whether each accession requires different conditions to break dormancy, batches of 100 seeds were stratifi ed at 5 °C for 10, 20, and 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…two years under fi eld conditions and require a period of cold to break dormancy. Under natural conditions, the seeds reach their highest germination percentage at 70 days after dispersal (Om et al, 2005). However, excess of soil humidity decreases their vigor and longevity, depending on their depth in the soil (Franke et al, 2007).…”
mentioning
confidence: 99%
“…Various factors affect the seed dormancy level of wild species. These types of study have been done principally with temperate climate species and have shown that the main stimulants are: light (Om et al, 2003), alternate temperatures (Ikeda et al, 2008;Ferreira e Rosa, 2009) and potassium nitrate (Chauhan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%